Electrodes Based on Zeolites Modified with Cobalt And/Or Molybdenum for Pesticide Degradation. Part I: Physicochemical Characterization and Efficiency of the Electrodes for o2 Reduction and H2o2 Production - Ureta-Zanartu, M; Fernandez-Vidal, F; Castro-Laroze, J (Springer New York LLC, 2019)
With the purpose of obtaining inexpensive electrodes for the degradation of organic pesticides by the electro-Fenton reaction, the required H2O2 being obtained by the 2-electron reduction of dissolved O2, we have prepared glassy carbon electrodes coated with a mixture of graphite with Mo- and/or Co-modified zeolites. Three zeolites were used, Linde type A (ZA), Faujasite (ZY), and MFI (ZSM5), whose maximum possible cation exchange, directly given by the Al/Si ratio, and their hydrophilicity increases in the order ZSM5 < ZY < ZA. The zeolites were modified with Mo and/or Co by the wet impregnation method and characterized by different techniques. The outer surfaces of the three Mo-modified zeolites showed Mo-containing grains (in ZA) or needles (in ZY and ZSM5), which could be largely washed away with hot water. Electrodes were made by depositing on a disc of glassy carbon (GC) a mixture of graphite, zeolite, and a binder. Quite unexpectedly, the cyclic voltammograms (CVs) of the three Mo-modified zeolites showed at least five pairs of anodic–cathodic peaks, which we assume are due to the presence of the Mo7O24 6− isopolyoxomolybdate anion, proceeding from the impregnating solution, and anchored on the zeolites’ surface. With a rotating ring-disc electrode, the highest efficiency for H2O2 production at − 0.2 VRHE, namely, 12.7%, was obtained with the GC/graphite-(CoMo-exchanged ZA) electrode, but this efficiency decreased with time. On the contrary, the three zeolites modified only with Mo were stable in 4-h electrolyses at − 0.2 VRHE and yielded the highest H2O2 concentrations, which we attribute to the Mo7O24 6− isopolyoxomolybdate anchored on the zeolites. The H2O2 yield was the same for the three Mo-modified zeolites, irrespective of their exchange capacity and hydrophobic/hydrophilic character. [Figure not available: see fulltext.]. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.